How Attitudes about Guns Develop over Time. (February 2022) - Shapira, Harel; Liang, Chen; Lin, Ken-Hou
Existing scholarship usually presents people's attitudes about guns as fixed and fully formed. Rarely are such attitudes examined as the outcome of social processes. As a result, while we know a great deal about what people think about guns, we know very little about the development of these beliefs. In this paper, we use a combination of surveys and life history interviews with a national sample of college students between the ages of 18 and 24 to examine how attitudes about guns develop in childhood and young adulthood. We find that while family gun ownership matters, positive attitudes about guns develop through active socialization that continues beyond childhood and is not reducible to family background. Relationships play a key role in this process, with changes in relationships often driving changes in attitudes about guns. Changes in attitudes about guns can take place in terms of both the content (what young adults think about guns) and the form (how young adults think about guns). In the transition to young adulthood, attitudes about guns develop from being articulated primarily as personal experiences connected to the activity of shooting guns or experiencing gun violence, to being articulated as political beliefs, connected to issues of regulation. These findings contribute to our understanding of gun attitudes by offering insights on not only what people think about guns but also how people come to think about guns in the ways that they do.